Sensitivity of Regional Water Supply Systems Models to the Level of Skeletonization – A Case Study from Apulia, Italy. (2015) - Arena, Claudio; Cannarozzo, Marcella; Fortunato, Antonino; Scolaro, Ignazio; Mazzola, Mario Rosario
Abstract: Simulation models supported by state-of-the-art software packages are nowadays available to explore operation rules of regional water supply systems or to select structural alternatives for improving long-term service performances. Given the, sometimes high, complexity of these systems, model calibration can become a lengthy procedure and many runs are necessary before obtaining convincing results. However, even after calibration, depending on system's complexity and the number of time steps investigated, a single run can take up to several minutes, even on state-of-the-art computers, so that simulation time can become a true bottleneck if such models are to be coupled with metaheuristic optimization techniques, such as genetic optimization. This paper investigates the possibility to reduce computational time through skeletonization of the models. The regional water supply system of Apulia, Southern Italy, was adopted as a case study and the software package AQUATOR was employed to model the system.